2023
DOI: 10.1021/acs.energyfuels.3c01663
|View full text |Cite
|
Sign up to set email alerts
|

Extractive Desulfurization in Microchannel Contactors Using Deep Eutectic Solvents: Optimization Using Central Composite Design (CCD) and Flow Pattern Mapping

Ahmad Reza Mahdavi,
Mohammad Amin Sobati,
Salman Movahedirad

Abstract: In the present study, the optimization of extractive desulfurization in the microchannels was investigated using a deep eutectic solvent (DES). The influence of some operating and microchannel geometrical parameters, including the initial sulfur concentration of fuel, the length of the microchannel, the DES flow rate, and the ratio of fuel to DES flow rate (RF/D), on sulfur removal was investigated using response surface methodology (RSM). Moreover, the flow pattern map in the microchannels was investigated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Many authors ,,, carried out kinetic studies on desulfurization with DES in their different experimental conditions. Some studies on EDS using DES published by different authors are shown in Table . Recent studies on EDS in microchannel contractors using DES have also been reported in literature. , Aghaei and Sobati also reported a comprehensive study on the sulfur compounds removal in middle distillate fuels via ionic liquids (IL) and DESs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors ,,, carried out kinetic studies on desulfurization with DES in their different experimental conditions. Some studies on EDS using DES published by different authors are shown in Table . Recent studies on EDS in microchannel contractors using DES have also been reported in literature. , Aghaei and Sobati also reported a comprehensive study on the sulfur compounds removal in middle distillate fuels via ionic liquids (IL) and DESs.…”
Section: Introductionmentioning
confidence: 99%
“…28−31 Recent studies on EDS in microchannel contractors using DES have also been reported in literature. 32,33 Aghaei and Sobati 34 also reported a comprehensive study on the sulfur compounds removal in middle distillate fuels via ionic liquids (IL) and DESs.…”
Section: Introductionmentioning
confidence: 99%